Hypocotyl-derived adventitious root in Boesenbergia rotunda: Histological insight and medium optimization - KHAIRUNNISA ABD. GHANI; SITI ZULAIHA AHAMAD AZHAR; NORZULAANI KHALID; NOR AZMA YUSUF (Smujo International, 2026)
Abstract. Ghani KA, Azhar SZA, Khalid N, Yusuf NA. 2026. Hypocotyl-derived adventitious root in Boesenbergia rotunda: Histological insight and medium optimization. Asian J Agric 10 (1): g100111. https://doi.org/10.13057/asianjagric/g100111. Boesenbergia rotunda, commonly known as fingerroot, is a medicinal ginger widely valued for its bioactive flavonoids such as panduratin A, cardamonin, and pinostrobin, which exhibit antimicrobial, antioxidant, and anticancer activities. Despite its importance, large-scale pharmaceutical use is constrained by low and inconsistent yields from rhizomes under field conditions. Adventitious Root (AR) cultures represent a promising alternative for scalable biomass and metabolite production, yet the potential of hypocotyl explants remains underexplored. This study investigated the effectiveness of different culture medium types in inducing AR formation from in vitro hypocotyls of B. rotunda. Hypocotyl explants were cultured for four weeks on solid and liquid half-strength Murashige and Skoog (½ MS) medium supplemented with 0.5 mg/L Naphthaleneacetic Acid (NAA) (n=6). Induction rate, root number, and root length were quantified. Results showed that liquid medium significantly enhanced AR induction, achieving 100% response compared to 95% in solid medium, with more than twice the number of roots (29.14±2.91 vs. 12.25±2.82) and nearly doubled root length (1.96±0.25 cm vs. 0.94±0.05 cm). Histological analysis confirmed that root apical meristems originated directly from pericycle cells adjacent to phloem tissues, evidencing direct organogenesis. These findings provide the first histological validation of hypocotyl-derived AR in B. rotunda and highlight the exciting potential of the liquid culture system for future biotechnological applications and metabolite production.